The Politics of the Body and the State: Sexual Violence in a Radical Feminist Perspective - Umina Marsyaro; Nandita Anggraini; Ika Arinia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Sexual violence against women is a social phenomenon that cannot be understood solely as an individual criminal act, but also as a manifestation of patriarchal power relations in society. This study aims to analyze sexual violence as a form of body politics from the perspective of Kate Millett's radical feminism, and examines the case of Baiq Nuril as a reflection of the unequal power relations between men and women. This study uses a qualitative method with a literature study approach related to sexual violence and radical feminist theory. The results show that sexual violence is part of a patriarchal system that places women in a subordinate position and makes women's bodies objects of control in power relations. The concept of politics of sex proposed by Kate Millet explains that sexual relations between men and women reflect the structure of domination in a patriarchal society. The case of Baiq Nuril shows how unequal power relations in the workplace can facilitate sexual harassment and how the legal system is still influenced by gender bias that has the potential to harm victims. Therefore, structural changes are needed in the legal system, public policy, and social awareness to eliminate the patriarchal culture that is at the root of various forms of sexual violence against women.